PENGARUH MOTIVASI PENYULUH TERHADAP PRODUKTIVITAS KELOMPOK SAPI POTONG - Sry Yenni Pateda; Fauzan Zakaria (Jambura Journal of Animal Science, 2023)
Penelitian bertujuan untuk mengetahui tingkat motivasi penyuluh, tingkat produktivitas kelompok dan pengaruh The purpose of this study was to determine the motivation of extension agents, group productivity and the relationship between motivation and group productivity in beef cattle business. From October to December 2022 this research was carried out. The survey method was used to obtain primary and secondary data, purposive sampling. Data analysis used is simple regression analysis. The results show a motivational value of 177.6. The productivity of the beef cattle business group is quite good with an average score of 170. The effect of motivation on the productivity of the beef cattle business group is 59.3%